Economic and Military Diplomacy between India and Europe for Military Industrial Cluster Sustainability - Ismiyatun Ismiyatun (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
The article is held to explore economic and military diplomacy between India and Europe, especially United Kingdom, Germany and France on link of inovation, technology transfer sustainability which is needed for its military industry as one of superior sector at Bangalore and hyderabad techno park. Economic diplomacy is obtained through improvement raw material militay industry export while  import as the other side is improved with joint production or venture as defense procurement procedure. Beside that, India and Europe are initiated joint committee forum on economic, trade, financial impenetrate bilateral or multilateral. Military diplomacy inclines exist as programme or project assitance for modern weapon is based on information technology Keywords: Economic and military diplomacy, technology cluster, military industry